Treatment of retinoblastoma in Sub‐Saharan Africa: Experience of the paediatric oncology unit at Gabriel Toure Teaching Hospital and the Institute of African Tropical Ophthalmology, Bamako, Mali. Issue 8 (26th April 2018) - Traoré, Fousseyni; Sylla, Fatou; Togo, Boubacar; Kamaté, Bakarou; Diabaté, Konimba; Diakité, Abdoul Aziz; Diall, Hawa; Dicko, Fatoumata; Sylla, Mariam; Bey, Pierre; Desjardins, Laurence; Gagnepain‐Lacheteau, Anne; et al.
Abstract: Background: Retinoblastoma (Rb) is the most common intraocular primary malignancy in children. In industrialised countries, the cure rate is about 95%. We present the results of a prospective study on the management of Rb in the paediatric oncology unit of Gabriel Touré Teaching Hospital and African Institute of Tropical Ophthalmology, from November 1, 2011 to December 31, 2015. Procedure: The aims of this prospective study were to evaluate the treatment of localised Rb, ocular prosthesis after enucleation, conservative management for bilateral Rb as well as survival rates in all patients. Patients with early stage Rb at diagnosis were included. The treatment was performed according to the retinoblastoma treatment guidelines of the French‐African Paediatric Oncology Group. Results: Eighty‐eight patients were included in the study. Sex ratio was 1:1 (M = 44, F = 44). Median age at diagnosis was 3 years (range: 2 months–5 years). Unilateral intraocular Rb was predominant (n = 50; 56.8%). Conservative treatments were performed on nine eyes in nine patients. Overall survival and event‐free survival of the entire cohort at the end of 4 years were 73% (95% CI 60.8–81.2%) and 59% (95% CI 47.9–69.5%), respectively, with a median follow‐up of 3.7 years (0.1–5.6 years). In conclusion, early enucleation in early stage of Rb can improve outcomes in resource‐limited countries. Delayed enucleation and refusal of adherence to treatment are still major concerns and remain a barrier to improving overall patient survival.